Narrative der Migration - Ezli, Özkan (Undisziplinierte Bücher, 2021)
The cultural history of German migration society is still unwritten, even though, since the 1960s, numerous interactions and aesthetic negotiations have taken place in literature, film, and in societal debates and theories that have driven the transformation of the political system. This volume opens up an unexpected perspective on informal relations and potentials that have so far received little attention.